Low Expression of the Polycomb Protein RING1 Predicts Poor Prognosis in Human Breast Cancer - Gao, Song; Wang, Si-Yu; Zhang, Xing-Da; Wu, Hao; Pang, Da (Frontiers in Oncology, 2021)
Background: To date, breast cancer remains the most common malignant tumor in women. In recent years, a growing number of studies on polycomb proteins, have been conducted. The Ring finger protein1 (RING1), an essential component of the polycomb family of proteins, plays vital roles in the tumorigenesis of various cancer types. However, further research is required in determining RING1 expression and prognostic value in breast cancer. Method: RING1 expression level in multiple cancer types was evaluated using the XENA and UALCAN databases. Real-time quantitative PCR (real-time qPCR) and immunohistochemistry (IHC) were used to confirm this expression. The prognostic value was analyzed using our follow-up data and the Kaplan-Meier plotter website. RING1 co-expressed genes and its promoter methylation level were calculated using the cBioPortal and UALCAN online tools. The gene ontology (GO) and the Kyoto encyclopedia of Genes and Genomes (KEGG) pathway enrichment were analyzed using the DAVID online analysis tool. Result: RING1 expression was upregulated in CHOL, ESCA, LIHC, and PCPG. However, its expression level was decreased in COAD, KICH, KIRP, THCA, and BRCA. RING1 low expression is an unfavorable prognostic factor in many cancer patients, especially in breast cancer patients. For breast cancer, the IHC result showed that RING1 protein expression significantly and negatively correlates with tumor size (P=0.029), LNM (P=0.017), TNM stage (P=0.016), ER (P=0.005), Ki67 (P=0.015), and p53 status (P=0.034). Moreover, the multivariate Cox regression model indicated that RING1 (P=0.038) and ER (P=0.029) expressions were independent prognostic markers for breast cancer. RING1 co-expressed genes were selected, and included HDAC10, PIN1, CDK3, BAX, and BAD. GO analysis and KEGG pathway analyses revealed that RING1 related genes, were mainly enriched in "regulation of transcription", "apoptotic process", "protein transport", "protein binding", "Notch signaling pathway" and "Homologous recombination". Conclusion: RING1 expression was downregulated in breast cancer and its low expression was associated with worse disease outcomes. RING1 may act as a new prognostic biomarker and therapeutic target for breast cancer.